A Beginner’s Guide to Molecular Identification of Seaweed - Giuseppe C. Zuccarello; Nicholas A. Paul (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2019)
The most rapidly expanding areas for seaweed production in the world are the tropics, including Indonesia, yet these areas are also where molecular identification of local marine flora has only been sporadically employed. Furthermore, a goal for the Government of Indonesia is to diversify the types of seaweed that are being utilized, targeting valuable products and, hand in hand, to develop aquaculture techniques for these species. Morphological methods for species identification in algae are complex or unreliable, due to simple morphologies and plasticity. Therefore, it is crucial that the correct identification is made for species and varieties of commercial interest so that growth and biochemical results can be compared and contrasted between locations, across environments and over time without taxonomic ambiguity. This guide presents entry level methodologies for sample collection, DNA preservation, DNA extraction, PCR, and analyses of DNA sequence data, as a first step in the genetic characterization of both well-known cultivated species and identification of different species with potential economic properties.